Gingerdead man - Corrigan, Maya (Corrigan, Maya. Five-ingredient mystery, 2020)
"This holiday season Bayport, Maryland, is a dead ringer for Victorian London. Val and her grandfather are taking part in the Dickens of a Holiday festival. Val is hosting a private tea party serving the festival's costumed volunteers, who range from Dickens divas like Madame Defarge and Miss Havisham to Ebenezer Scrooge and old St. Nick himself. But one costumed reveler may have gotten the holidays mixed up. The winner of the creepiest outfit, robed in black with a gift bag covering the head - okay, Ghost of Christmas Present, Val gets it - hands out gingerbread men with white icing skeleton bones. This year's sour Santa has none of the big fellow's mirth but plenty of his appetite, and it's no secret Santa loves cookies. But when the man in red turns blue, Val and Granddad have a cookie-cutter killer to catch before the New Year . . ."--Publisher.